Three Decades of Social Work in France: from Security within the Welfare State to a State of «Disembedded Modernity» - John Ward (Social Work & Society, 2006)
Over the past three decades a great deal of controversy, debate and uncertainty has developed about the status of social work in French society and about the need to redefine its fundamental aims. In this article, I will attempt to describe some of the main trends and to elucidate some of the historical reasons for this state of self-doubt among social work professionals and for the criticisms they have faced from representatives of the public authorities over the past two decades. These are due, in part, to changes specific to the French context where social work has evolved from a mainly generic role governed by the central state to a mainly project based, needs led activity controlled by decentralised public bodies and non governmental agencies. On a broader level, I will also suggest that changes and self questioning in social work are symptoms of a form of "disembedded modernity" as analysed by contemporary sociologists such as Anthony Giddens, whose analyses correspond in some ways to those of some contemporary French sociologists influential in the world of social work.